207k views
2 votes
80g + 30h = 10(g + h)

User Zigarn
by
5.2k points

2 Answers

5 votes

Assignment:
\bold{Simplify \ Expression: \ 80g+30h=10\left(g+h\right)}

<><><><><><><>

Answer:
\boxed{\bold{g=-(2h)/(7)}}

<><><><><><><>

Explanation:
\downarrow\downarrow\downarrow

<><><><><><><>

[ Step One ] Expand
\bold{10\left(g+h\right): \ 10g+10h}


\bold{80g+30h=10g+10h}

[ Step Two ] Subtract 30h From Both Sides


\bold{80g+30h-30h=10g+10h-30h}

[ Step Three ] Simplify


\bold{80g=10g-20h}

[ Step Four ] Subtract 10g From Both Sides


\bold{80g-10g=10g-20h-10g}

[ Step Five ] Simplify


\bold{70g=-20h}

[ Step Six ] Divide Both Sides By 70


\bold{(70g)/(70)=(-20h)/(70)}

[ Step Seven ] Simplify


\bold{g=-(2h)/(7)}

<><><><><><><>


\bold{\rightarrow Mordancy \leftarrow}

User Robert
by
4.7k points
3 votes

Answer:


g= -(7)/(2)

Explanation:

80g + 30h = 10g + 10h

70g = -20h

g =
-(70)/(20) = -(7)/(2)

User Samiul Amin Shanto
by
5.1k points